Agglomeration and the adjustment of the spatial economy (2005)
We consider the literatures on urban systems and New Economic Geography to examine questions concerning agglomeration and how areas respond to shocks to the economic environment. We first propose a diagrammatic framework to compare the two approaches. We then use this framework to study a number of extensions and to consider several policy relevant issues.